Lean mass and fat mass have differing associations with bone microarchitecture assessed by high resolution peripheral quantitative computed tomography in men and women from the Hertfordshire Cohort Study - Edwards, Mark H (Bone, 2015)
Understanding the effects of muscle and fat on bone is increasingly important in the optimisation of bone health. We explored relationships between bone microarchitecture and body composition in older men and women from the Hertfordshire Cohort Study. 175 men and 167 women aged 72-81 years were studied. High resolution peripheral quantitative computed tomography (HRpQCT) images (voxel size 82μm) were acquired from the non-dominant distal radius and tibia with a Scanco XtremeCT scanner. Standard morphological analysis was performed for assessment of macrostructure, densitometry, cortical porosity and trabecular microarchitecture. Body composition was assessed using dual energy x-ray absorptiometry (DXA) (Lunar Prodigy Advanced). Lean mass index (LMI) was calculated as lean mass divided by height squared and fat mass index (FMI) as fat mass divided by height squared. The mean (standard deviation) age in men and women was 76 (3) years. In univariate analyses, tibial cortical area (p<0.01), cortical thickness (p<0.05) and trabecular number (p<0.01) were positively associated with LMI and FMI in both men and women. After mutual adjustment, relationships between cortical area and thickness were only maintained with LMI [tibial cortical area, β(95% confidence interval (CI)): men 6.99 (3.97,10.01), women 3.59 (1.81,5.38)] whereas trabecular number and density were associated with FMI. Interactions by sex were found, including for the relationships of LMI with cortical area and FMI with trabecular area in both the radius and tibia (p<0.05). In conclusion, LMI and FMI appeared to show independent relationships with bone microarchitecture. Further studies are required to confirm the direction of causality and explore the mechanisms underlying these tissue-specific associations.